Paleoecological Studies at the Ancient Maya Center of Yaxnohcah Using Analyses of Pollen, Environmental DNA, and Plant Macroremains - Lentz, David L.; Hamilton, Trinity L.; Dunning, Nicholas P.; Jones, John G.; Reese-Taylor, Kathryn; Anaya Hernández, Armando; Walker, Debra S.; Tepe, Eric J.; Carr, Christopher; Brewer, Jeff L.; Ruhl, Thomas; Meyers, Stephanie A.; et al. (Frontiers in Ecology and Evolution, 2022)
Yaxnohcah was a major city of the ancient Maya world, especially during the Preclassic period (1000 BCE-200 CE). Data from excavations provide important insights into the interactions between the ancient inhabitants of this polity and its surrounding Neotropical forests, a topic that, as a whole, remains largely enigmatic. This study aspired to fill that void in understanding by using traditional paleoethnobotanical approaches and a powerful new technology, the analysis of environmental DNA. Our results enabled us to characterize the vegetation growing in association with the principal structures and the artificial reservoirs that provided the city’s water supply. Because the area is without access to permanent water sources, such as rivers or lakes, these reservoirs were key to the development and survival of the city. Our results indicate that although there were large areas cleared for agricultural purposes, a mosaic of mature upland and bajo forest remained throughout the Maya occupation. In addition, our studies reveal that there were incursions of pine savanna into the area that may have been a reflection of prevailing edaphic conditions, or alternatively, the result of frequent burning.